The conceptual model of the construction project taking into account the interests of stakeholders - Dorokhina, А.; Starostina, А.; Artiukh, R. (Національний технічний університет "Харківський політехнічний інститут", 2018)
The subject matter of the article components of the scope of investment and construction projects and the interests of its stakeholders. The goal of the article is to develop the concept of application of the value approach while forming construction projects. The article deals with the following tasks: the impact of the factors of the external and internal situation of the construction project on the process of its management is analyzed, unsolved methodological problems in the field of scope management reviewed, the conceptual model of the construction project is developed taking into account socio-cultural factors. The following methods are used: the methodology of project management, the theory of stakeholders, axiological and system approaches. The following results are obtained: the structure of elements of the scope of the conceptual model of the construction project is developed, taking into account the interests of the stakeholders; the influence of various factors on the scope of the construction project is considered; the environment of the construction project is systematized, numerous factors are classified as external and internal, stable and variable one; the impact of social and cultural factors on the construction project is analyzed; a set of stakeholders ininvestment and construction projects was defined, this set is divided into groups of direct and indirect impact on the project scope. From the point of view of the degree of the impact of stakeholders on the project and its objectives, indicators according to which stakeholders have their own interests are determined. The scheme is constructed that shows the correspondence of stakeholders to the areas of project interest. Stakeholder interests are suggested to be considered during the full life cycle of the investment and construction project. The scheme of the spheres of the interests of participants in the investment and construction project at separate stages of its life cycle is constructed. When forming the scope of investment and construction projects, the axiological approach should be applied, that is, to take into account the interests of stakeholders that affect the performance of the project during the whole period of the life cycle.

Предметом дослідження в статті є складові змісту інвестиційно-будівельних проектів та інтереси його стейкхолдерів. Мета роботи - розробка концепції застосування ціннісного підходу при формуванні будівельних проектів. В статті вирішуються наступні завдання: аналіз впливу факторів зовнішнього та внутрішнього оточення будівельного проекту на процес його управління, огляд невирішених методологічних проблем у сфері управління змістом, розробка концептуальної моделі будівельного проекту з урахуванням соціокультурних факторів. Використовуються такі методи: методології управління проектами, теорія стейкхолдерів, теорія цінностей, системний підхід. Отримано наступні результати: розроблено структуру елементів змісту концептуальної моделі будівельного проекту з урахуванням інтересів стейкхолдерів. Розглянуто вплив різноманітних факторів на зміст проекту будівництва. Проведено систематизацію оточення будівельного проекту у вигляді класифікації множини факторів на зовнішні та внутрішні, на стабільні і змінювані. Проаналізовано вплив соціокультурних чинників на зміст будівельного проекту. Визначено множину стейкхолдерів інвестиційно-будівельних проектів, яку поділено на групи прямого та непрямого впливу на зміст проекту. З точки зору ступеню впливу стейкхолдерів на проект та його цілі, визначено показники, за якими стейкхолдери мають власні інтереси. Побудовано схему відповідності стейкхолдерів зонам інтересів проекту. Запропоновано розглядати інтереси стейкхолдерів на протязі повного життєвого циклу інвестиційно-будівельного проекту. Побудовано схему сфер інтересів учасників інвестиційно-будівельного проекту на окремих етапах його життєвого циклу. При формуванні змісту інвестиційно-будівельних проектів слід застосовувати ціннісний підхід, тобто враховувати інтереси стейкхолдерів,які впливають на виконання робіт проекту протягом усього життєвого циклу.
Концептуальна модель проекту будівництва з урахуванням інтересів стейкхолдерів
Keywords: social factors; cultural factors; project value; life cycle; цінність проекту; життєвий цикл